Heideggers Denken: Anmerkungen zur Rezeptionsgeschichte der Philosophie - Trawny, Peter (2021)
This article approaches the problematizing of the Reception of Heidegger’s thought and the way in which philosophical practice has been carried out in the university environment. It is about supporting the thesis that the great relevance of Heidegger's thought consists in defending the autonomy of thought in relation to other forms of manifesting existence. In this sense, the History of Philosophy was consolidated, in spite of what is sought to defend here, as a history of receptions, strongly determined by the objectification of thinking and the maintenance of fixed actuation structures. Thus, we intend to show that Heidegger's philosophy preserves an important instrument to fight against the sedimentation of thinking into works, against the stagnation of philosophical activity itself.Keywords: Heidegger. History of Philosophy. Philosophical Reception.